When money does not matter or the Aprista monetary policy, Peru: 1985-1988 - Morón Pastor, Eduardo Andrés (1989)
In this article the author presents a critical viewpoint to many of the monetary policies during the firts three and a half years of the aprista government. In this way, such policies have as a common characteristic the modeling assumption that "money does not matter", which means the irrelevancy of its effects over the diferent macroeconomic variables. Throughout this article, the author works out some points which lead to the conclusion that the present crisis is due to a set of mistakes, not only because of the economic instruments, but the theoretical frame about the importance and the effect of money on the economy.